Entrepreneurial intent among information systems students: investigating the role of family context, self-employment and gender in undergraduate education - Coelho, Moises Israel Belchior de Andrade; Lira, Elsianne Serudo Marinho (Brazilian Journal of Production Engineering, 2021)
This research aims to investigate family background, self-employment, and gender in undergraduate students of information systems. Regarding the approach to the problem, this research is characterized as quantitative and as for the objectives, there is exploratory research. The technical procedure adopted was the case study in information systems students (number of respondents equal to 100). The main results that most students intend to become entrepreneurs in the future: Students who have a family background tend to support entrepreneurship more; and high entrepreneurial behavior in females concerning males. The importance of this study is to indicate how such factors (family background, self-employment, and gender) affect undergraduate students, contributing to the theoretical and managerial aspects of studies in entrepreneurial intention in the context of the Amazonia region.
Keywords: Entrepreneurial intention; Information systems students; Family background; Gender; Self-employment